0131 Decreased Habitual Sleep Efficiency is Associated with Increased Insulin Resistance in Healthy Adult Men. (27th May 2020) - Kelly, M R; O'Byrne, N; Iranmanesh, A; Martin, J L; Liu, P Y
Abstract: Introduction: Partial sleep deprivation is associated with increased insulin resistance (IR), a metabolic disease risk marker. Little is known about habitual sleep patterns and IR in the absence of acute sleep restriction. We anticipated greater change in habitual sleep over one month would be associated with increased IR. Methods: 24 males (age=33.6±6.4 years; BMI=25.7±2.5kg/m 2 ) completed baseline (T1) and follow-up (T2; ≥4 weeks post-T1) study procedures: actigraphy (one week) followed by polysomnography (PSG; one 10h sleep opportunity) and a next morning oral glucose tolerance test (OGTT; homeostatic model assessment insulin resistance [HOMA-IR], β-cell function [HOMA-β], and Matsuda Index). Weekly average actigraphy total sleep time (aTST; 291-511min) and sleep efficiency (aSE; 72–93%) were computed at T1 and T2, as well as across the 1, 2, and 3 days prior to PSG/OGTT. Pearson and Spearman correlations assessed the change (T1-T2) in actigraphy (aSEΔ, aTSTΔ, PSGΔ) or PSG sleep (PSG-TSTΔ, PSG-SEΔ, sleep stages) versus change in metabolic risk (HOMA-IRΔ, HOMA-βΔ, MatsudaΔ). Results: There were significant correlations between HOMA-IRΔ and aSEΔ [ r (22)=-0.42, p =0.01; r s =-0.45, p =0.03], PSG TSTΔ [r(22)=0.50, p=0.012; r s =0.41, p=.045], and PSG-SEΔ [r(22)=0.49, p=0.015; r s =0.43, p=.037]. No significant associations emerged between change in metabolic risk versus aTSTΔ one week prior to PSG/OGTT, aSEΔ or aTSTΔ across 1–3 days prior to PSG/OGTT, or PSG sleep stages. Conclusion: Within-subject T1-T2 decrease in habitual sleep quality, but not TST, was associated with increased IR. T1-T2 PSG TST and SE were associated with following day IR. At home sleep 1–3 days beforehand were not correlated with IR. Although preceding night sleep quality and TST are associated with IR, habitual sleep quality, rather than TST, may be a more important determinant of metabolic risk in community dwelling middle-aged men. Support: This work was supported by NIH/NHLBI R01HL124211, NIH/NHLBI K24HL138632, NIH National Center for Advancing Translational Sciences (NCATS) UCLA CTSI Grant UL1TR001881 (PI: Liu); and NIH/NHLBI K24HL143055 (PI: Martin). Dr. Kelly is supported by the VA Office of Academic Affiliations through the Advanced Fellowship Programs in Geriatrics.